Blockchain based integrated security measure for reliable service delegation in 6G communication environment - Manogaran, Gunasekaran; Rawal, Bharat S.; Saravanan, Vijayalakshmi; Kumar, Priyan Malarvizhi; Martínez, Oscar Sanjuán; Crespo, Rubén González; Montenegro-Marin, Carlos Enrique; Krishnamoorthy, Sujatha (Computer communications, 2020)
Sixth generation (6G) communication environment is unfolded in the recent years in order to provide high throughput less latency services for the mobile users. This environment encloses a variety of heterogeneous resources and communication standards to ensure seamless availability of services. In this open environment, security is a concerning issue due to heterogeneous standard integration and access delegations. This paper introduces blockchain-based integrated security measure (BISM) for providing secure access control and privacy preserving for the resources and the users. The access control process relies on the states of the virtualized resources at different time instances and the privacy preserving relies on longevity of service responses. The access delegation and denial is decided by the changeover of the states of the resources as aided by the Q-learning procedure for improving the service related performance. This performance for access control and privacy is verified using the metrics true positives, access denial and success ratio, access time and modification, memory utilization and time complexity.